SIKAP FOLLOWERS TERKAIT NURHADI-ALDO DALAM MEDIA SOSIAL INSTAGRAM DAN TWITTER - Aulia Ayuningtyas; Nuriyatul Lailiyah (Interaksi Online, 2019)
Nurhadi-Aldo is one of the political humor accounts in Indonesia. Nurhadi-Aldo is known as a fictitious candidate to attract the attention of many people. This account is widely discussed because the content is quite entertaining and unique. The content produced by Nurhadi-Aldo is a persuasive message where he inserts an invitation to choose himself as a candidate. This triggers pros and cons in the community. This account comes amid the heat of the presidential election atmosphere which is divided into two camps namely Jokowi and Prabowo. The emergence of this phenomenal account then caused a stir in the community. There are those who take it seriously and some who take it easy. This has led to different attitudes and emerged during the presidential election. This research can be explained through the Elaboration likelihood model theory, which can predict attitudes from persuasive messages. Sampling in this study was carried out using incidental sampling techniques. This research is a case study type using qualitative descriptive analysis. The results of this study indicate the informants used the two channels of persuasion message processing in the @ Nurhadi-Aldo account, namely the central and peripheral paths. The peripheral processing channel appears marked by the interest of the informants towards funny pictures and memes about Nurhadi-Aldo, while the central channel arises when the informants involve their critical thinking to make many considerations before changing their attitudes. From both lanes, the informants in this study were dominant using the central lane. From the two uses of the persuasion message processing channel arises changes in attitude involving cognitive, affective and conative responses in each individual. The dominant attitude that appears tends to be negative because the results of information processing indicate that more informants do not support Nurhadi-Aldo.